2005
DOI: 10.1074/jbc.m506855200
|View full text |Cite
|
Sign up to set email alerts
|

The inv(16) Cooperates with ARF Haploinsufficiency to Induce Acute Myeloid Leukemia

Abstract: The inv(16) is one of the most frequent chromosomal translocations associated with acute myeloid leukemia (AML) and creates a chimeric fusion protein consisting of most of the runt-related X1 co-factor, core binding factor ␤ fused to the smooth muscle myosin heavy chain MYH11. Expression of the ARF tumor suppressor is regulated by runt-related X1, suggesting that the inv (16) The gene encoding the runt-related-X1 (RUNX1, 3 also known as acute myeloid leukemia 1 (AML1)) transcription factor is one of the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
1
12
0
1
Order By: Relevance
“…This provides a novel rationale for the loss of function of this gene in tumors. In this connection, a loss of heterozygosity of the CDKN2a locus promotes tumor progression significantly in both mouse and human contexts, revealing a haploinsufficiency effect and validating the importance of the ϳ2-fold regulation of p14ARF expression observed here (24,40,52,62). The pro-anoikis effect of p14ARF also may explain the advantage to tumor cells of overexpressing TBX2/3 and/or NRAGE proteins-repressors of p14ARF that counteract anoikis and promote anchorage-independent growth (10, 42, 96)-or other repressors of p14ARF (49).…”
Section: Discussionmentioning
confidence: 96%
“…This provides a novel rationale for the loss of function of this gene in tumors. In this connection, a loss of heterozygosity of the CDKN2a locus promotes tumor progression significantly in both mouse and human contexts, revealing a haploinsufficiency effect and validating the importance of the ϳ2-fold regulation of p14ARF expression observed here (24,40,52,62). The pro-anoikis effect of p14ARF also may explain the advantage to tumor cells of overexpressing TBX2/3 and/or NRAGE proteins-repressors of p14ARF that counteract anoikis and promote anchorage-independent growth (10, 42, 96)-or other repressors of p14ARF (49).…”
Section: Discussionmentioning
confidence: 96%
“…This observation, and the correlation between the expression of ankyrin-G and p14ARF in breast cancer cell lines, suggests that p14ARF is an important determinant of anoikis sensitivity (Kumar et al, 2011). This may also constitute an underlying reason for the widespread loss of p14ARF in human cancers and the observation that even heterozygosity for wild-type p14ARF correlates strongly with tumor incidence (Hewitt et al, 2002;Moreno-Miralles et al, 2005). Although p14ARF was originally shown to induce apoptosis through p53, p53-independent mechanisms that involve its interaction with the Myc proto-oncogene, the generalized EMT-mediating co-repressor protein, C-terminal binding protein (CTBP) or the mitochondrial p32 protein have now been shown (Itahana and Zhang, 2008;Paliwal et al, 2006;Qi et al, 2004).…”
Section: The Role Of E-cadherin In Anoikismentioning
confidence: 90%
“…Until recently, the chimeric protein CBFh-SMMHC had been known primarily for its ability to block differentiation presumably by inhibiting transcription of myeloid-specific genes through dominant repression of CBF transcription factors (31,32). Very recently, it was shown that CBFh-SMMHC can suppress expression of ARF by impairing RUNX1-mediated activation of the promoter in HeLa cells (33). These data along with ours suggest that CBFh-SMMHC induces leukemia in part by affecting the cell cycle and apoptosis through inhibition of the p53 and the Rb pathways.…”
Section: Discussionmentioning
confidence: 99%